A drug awareness program for use with adolescents in Lebanese schools - Solh, Karma Abdel-Salam (Beirut Lebanese American University. School of Arts and Sciences. Education Department, 2008)
In this study, a drug awareness program was developed for adolescents in Lebanese schools. Questionnaires and interviews were conducted with students and school counselors in two schools in Lebanon. The results were compared with the review of literature on drug awareness programs, which produced a program that was adapted to the adolescents in Lebanon. The drug awareness program that was developed includes the components of an awareness program, the different roles that key people play in an awareness program, and methods of implementing the awareness program in the school.
: Mémoire
Keywords: Adolescents; Adolescents; Education Sanitaire; Health education Intervention Programs; Programme des interventions